2013
DOI: 10.1039/c3ee40697k
|View full text |Cite
|
Sign up to set email alerts
|

Current density dependence of peroxide formation in the Li–O2 battery and its effect on charge

Abstract: We report a significant difference in the growth mechanism of Li 2 O 2 in Li-O 2 batteries for toroidal and thin-film morphologies which is dependent on the current rate that governs the electrochemical pathway. Evidence from diffraction, electrochemical, FESEM and STEM measurements shows that slower current densities favor aggregation of lithium peroxide nanocrystallites nucleated via solution dismutase on the surface of the electrode; whereas fast rates deposit quasi-amorphous thin films. The latter provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

69
672
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(748 citation statements)
references
References 33 publications
69
672
5
2
Order By: Relevance
“…The Ag 9 toroids are smaller than the Ag 15 toroids (B500 nm versus B1,000 nm) with the same discharge capacity. Toroids have been found in the discharge product by others in Li-O 2 cells [31][32][33][34] . The X-ray diffraction (XRD) patterns in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag 9 toroids are smaller than the Ag 15 toroids (B500 nm versus B1,000 nm) with the same discharge capacity. Toroids have been found in the discharge product by others in Li-O 2 cells [31][32][33][34] . The X-ray diffraction (XRD) patterns in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] [14,15] A number of studies have attributed the formation of large Li 2 O 2 particles and high discharge capacities observed at low rates (< 10 mA cm À2 in ethers [16,17] ), to high availability of soluble Li + -O 2 À . Abraham and co-workers [13,14,18] have suggested that the stability of Li + -O 2 À increases with solvent donor number (DN), which is a measure of the solvation enthalpy of the Lewis acid SbCl 5 in a given solvent .…”
mentioning
confidence: 99%
“…In the absence of DBBQ, reduction of O 2 to Li 2 O 2 proceeds via the LiO 2 intermediate 15,16,[18][19][20][21] , and it is the need to reach the potential for formation of LiO 2 that pins the O 2 reduction at a potential (discharge plateau in a Li-O 2 cell) significantly negative of the standard potential for Li 2 O 2 formation, 2.96 V (Fig. 1).…”
Section: The Mechanism Of O 2 Reduction In the Presence Of Dbbqmentioning
confidence: 99%
“…In contrast, if Li 2 O 2 can be induced to grow in the electrolyte solution then high discharge capacities at relatively high rates and avoiding early cell death is possible 15 . It is clearly important to operate a Li-O 2 battery in which Li 2 O 2 grows in solution.A number of groups have elucidated the mechanism of O 2 reduction to Li 2 O 2 on discharge 15,16,[18][19][20][21] . The reduction proceeds through the following general steps: 22,[27][28][29][30] .…”
mentioning
confidence: 99%
See 1 more Smart Citation